READING MEMORY SITES THROUGH SIGNS ([S.l.])
1 online resource
Keywords: What can space tell us about our past? Which stories do memory sites narrate? Which memories do they transmit? And, more importantly, how can we read their meanings? Semiotics can provide us with a homogeneous, shareable and theoretically sound methodology to analyse space within a comparable and common frame of reference for scholars of memory studies and traumatic heritage, as well as for historians, architects and museum curators. The book describes in clear and understandable language the main semiotic concepts that can be used to analyse space, illustrating them with carefully chosen case studies of memory spaces - monuments, museums, post-war urban restoration, filmed and virtual space - in order to show the applicability and efficacy of a semiotic methodology.